Detection of suspicions of Varicose veins in the legs using thermal imaging - Meneses Claudio, Brian (2019)
Varicose veins also known as venous insufficiency, are dilated veins due to an accumulation of blood that occurs in different parts of the body, the most common are in the legs, in addition to having a higher index in women for clothing style that they use. Varicose veins are classified by grades ranging from I to IV and can cause pain, itching, cramps and even ulcers if they are treated in time. Not all varicose veins can be visible superficially, many of them begin inside of the skin. According to the WHO (World Health Organization) 10% of the world population has varicose veins. That is why the detection of suspicions of varicose veins in the legs was raised in this research work, first a thermal image will be obtained using the FLIR ONE Pro thermal camera following a necessary protocol of distance and temperature range. The thermal image is processed in MATLAB to identify the segments of the histogram of the thermal image, to obtain the area of the highest temperature indicating the presence of varicose vein in the subject's leg. The segmentation of the areas with the highest temperature was obtained as a result to be overlaid on the real image, showing the real image with the varicose vein segment found in the thermal image processing.